Exploring the relationship between L2 vocabulary size and academic speaking. (July 2022) - Wang-Taylor, Yixin; Clenton, Jon
Abstract: The current paper explores second language (L2) learners' academic vocabulary size and its potential relationship to speaking in academic contexts. Our participants were 62 first language (L1) Chinese undergraduates of intermediate English level. We elicited speech samples from monologue tasks in formal class settings. We elicited vocabulary knowledge using two yes/no tests, X_Lex (Meara & Milton, 2003 ) and the Academic Vocabulary Size Test (AVST; Masrai & Milton, 2018 ), measuring general and academic vocabulary size, respectively. Our results indicate that AVST scores correlate moderately significantly with several speaking fluency measures and band-based frequency measures of vocabulary use, which outperform the explained variance of X_Lex. The mid-frequency words (K3) forming 56% of the academic words list is perhaps the primary force for the strong predictive strength of the AVST. These findings provide critical pedagogical implications for L2 academic vocabulary learning and teaching in English for Academic Purposes (EAP) classrooms. The AVST emerges as a potential assessment to predict L2 speaking in academic contexts. We discuss future possible research directions with particular reference to vocabulary research in practice. Highlights: Strong predictive power of academic vocabulary size to measures of speaking fluency. Academic vocabulary size outperforms general vocabulary size to academic speaking. Vocabulary size predicts lexical diversity/lexical sophistication in academic speech. Knowing mid-frequency words helps produce words suitable in academic contexts.